Cost Control Strategies For Ibs Contractors In Malaysia - Lew, Yoke Lian (2002)
Industrialised Building System (IBS) is a system widely used in construction industry in Malaysia. This study is a survey to identify the factors contributing to cost control problems faced by local contractors in IBS projects and to identify the strategies used to reduce the cost variation in IBS projects. From the finding of the survey, a computer-based cost control model was developed to improve the effectiveness of cost control on IBS. The survey shows that management team capability & performance, buildability of design, and timely decision making were the top-ranked factors contributing to cost control problems in IBS construction in Malaysia. Strategies like increase the working hours, increase manpower and/or equipment, provide close supervision to subordinates for minimising abortive work, and coordinate closely with subcontractors were identified as the most popular method used to reduce cost variation of IBS projects. In hypotheses testing of this study, it was found that there is significant association between type of IBS used and the perceived contributor to cost control problems.Results of Logistic Regression Analysis shows that allowance of partially handover, delay of payment from client to the contractor, deposit needed for IBS before delivery of the precast components, and application of tracking curve for cost control are likely to influence the cost variance of IBS construction projects. The developed computer-based cost control model could assist constructor of IBS (with prefabricated elements) to plan their expenses and progress of work. Additionally, monitoring during the construction is made available through a series of user-friendly electronic forms. With identification of potential problem contributors, strategies to overcome cost variation, and application of the cost control model, cost control of IBS projects in Malaysia would be unproblematic to any new or existing IBS practitioners.